Dynamic tumor tracking using the Elekta Agility MLC. Issue 11 (31st October 2014) - Fast, Martin F.; Nill, Simeon; Bedford, James L.; Oelfke, Uwe
Abstract : Purpose: To evaluate the performance of the Elekta Agility multileaf collimator (MLC) for dynamic real‐time tumor tracking. Methods: The authors have developed a new control software which interfaces to the Agility MLC to dynamically program the movement of individual leaves, the dynamic leaf guides (DLGs), and the Y collimators ("jaws") based on the actual target trajectory. A motion platform was used to perform dynamic tracking experiments with sinusoidal trajectories. The actual target positions reported by the motion platform at 20, 30, or 40 Hz were used as shift vectors for the MLC in beams‐eye‐view. The system latency of the MLC (i.e., the average latency comprising target device reporting latencies and MLC adjustment latency ) and the geometric tracking accuracy were extracted from a sequence of MV portal images acquired during irradiation for the following treatment scenarios: leaf‐only motion, jaw + leaf motion, and DLG + leaf motion. Results: The portal imager measurements indicated a clear dependence of the system latency on the target position reporting frequency. Deducting the effect of the target frequency, the leaf adjustment latency was measured to be 38 ± 3 ms for a maximum target speed v of 13 mm/s. The jaw + leaf adjustment latency was 53 ± 3 at a similar speed. The system latency at a target position frequency of 30 Hz was in the range of 56–61 ms for the leaves ( v ≤ 31 mm/s), 71–78 ms for the jaw + leaf motion ( v ≤ 25 mm/s), and 58–72 ms for the DLG + leaf motion ( v ≤ 59 mm/s). The tracking accuracy showed a similar dependency on the target position frequency and the maximum target speed. For the leaves, the root‐mean‐squared error (RMSE) was between 0.6–1.5 mm depending on the maximum target speed. For the jaw + leaf (DLG + leaf) motion, the RMSE was between 0.7–1.5 mm (1.9–3.4 mm). Conclusions: The authors have measured the latency and geometric accuracy of the Agility MLC, facilitating its future use for clinical tracking applications.